Rachel Nordlinger: Constructive Case : Evidence from Australian Languages - Butt, Miriam (My University, 2000)
Rachel Nordlinger presents an approach to case marking that is characterized by an in- depth knowledge of Australian languages, a solid theoretical foundation, and a central idea that is startlingly simple to grasp. By the end of the book, vagaries of Australian case Systems such äs case marking that is spread over discontinuous constituents, case stacking of up to four differing markers in a row, and the use of case markers to convey tense/aspect/mood Information appear to the reader to be an eminently sensible way of organizing a language. The first two introductory chapters lay out the basics of the formal framework assumed by Nordlinger and then go on to provide an overview and summary of the nonconfigurationality issue that has long accompanied discussions of the structure and characteristics of Australian languages. Nordlinger situates her views on case squarely …
Keywords: Australische Sprachen; Kasusgrammatik; Syntax; 400